1974
DOI: 10.1128/jvi.13.3.740-752.1974
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Reovirus Oligo Adenylic Acid In Vivo and In Vitro

Abstract: mM), pyruvate kinase (25 tLg/ml), and actinomycin D (10 ,g/ml) were added to all reaction mixtures. (ii) Chymotrypsin (100 sg/ml) was added to the reaction 740

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Furthermore, the synthesis of oligoadenylates may then be an expression of a partial activity of the transcriptase in the process of being inactivated: its Km for adenosine triphosphate may then greatly exceed that for other nucleoside triphosphates, which would result in its catalyzing the template-independent polymerization of adenosine triphosphate to short oligoadenylates. Indeed, Silverstein et al (95) found that oligoadenylates are formed within nascent virus particles during the final stages of morphogenesis and suggested that the oligoadenylate polymerase activity may be an alternative activity of the viral transcriptase regulated by outer capsid proteins. Furthermore, Johnson et al (36) found that late temperature-sensitive mutants of reovirus that synthesize noninfectious and therefore presumably defective particles at nonpermissive temperatures do not synthesize oligoadenylates at nonpermissive temperatures, which again supports the conclusion that they are synthesized during the final stages of virus maturation.…”
Section: Transcription Of Reovirus Ribonucleic Acidmentioning
confidence: 99%
“…Furthermore, the synthesis of oligoadenylates may then be an expression of a partial activity of the transcriptase in the process of being inactivated: its Km for adenosine triphosphate may then greatly exceed that for other nucleoside triphosphates, which would result in its catalyzing the template-independent polymerization of adenosine triphosphate to short oligoadenylates. Indeed, Silverstein et al (95) found that oligoadenylates are formed within nascent virus particles during the final stages of morphogenesis and suggested that the oligoadenylate polymerase activity may be an alternative activity of the viral transcriptase regulated by outer capsid proteins. Furthermore, Johnson et al (36) found that late temperature-sensitive mutants of reovirus that synthesize noninfectious and therefore presumably defective particles at nonpermissive temperatures do not synthesize oligoadenylates at nonpermissive temperatures, which again supports the conclusion that they are synthesized during the final stages of virus maturation.…”
Section: Transcription Of Reovirus Ribonucleic Acidmentioning
confidence: 99%
“…Five other enzymatic activities have been detected in the virus particle (36). Only one, the polyadenylic acid [poly(A)] polymerase (34,38), is active when the virus is complete. The remaining four are manifest only in viral cores or subviral particles.…”
mentioning
confidence: 99%